"Cascades, torrents & drowning" in information: seeking help in the contemporary general practitioner practice in the UK. Issue 5 (3rd July 2016) - Holley, Debbie; Santos, Patricia; Cook, John; Kerr, Micky
ABSTRACT: This paper responds to the Alpine Rendez-Vous "crisis" in technology-enhanced learning. It takes a contested area of policy as well as a rapid change in the National Health Service, and documents the responses to "information overload" by a group of general practitioners practices in the North of England. Located between the spaces identified by Traxler and Lally as "competitive industrialisation" and web 1.0, and the consumer/ customer focus and ubiquitous ownership enabled by portable and devices and web 2.0, in this work we see the parallels of the responses of publicly funded bodies moving towards privatisation as part of a neo-liberal agenda. Interviews with health professionals (HPs) revealed marginalised spaces for informal learning in their workplaces, and a desire to build a community that would enable them to overcome the time/space barriers to networking. The EU Learning Layers Integrating Project develops mobile and social technologies that unlock and enable peer production within and across traditional workplace boundaries. Through the HP narratives, we capture insights into their daily life, which enable the articulation of their needs for an online "Help-seeking" networking service, underpinned by their desire to consult what Vygotsky calls "the more capable peer."